2019
DOI: 10.2174/1874364101913010043
|View full text |Cite
|
Sign up to set email alerts
|

Same-Site Deep Sclerectomy Re-Operation with Subconjunctival and Subscleral Collagen Matrix (Ologen™) and Minimal use of Mitomycin C

Abstract: Purpose: This study aimed to evaluate the safety and efficacy of same-site Deep Sclerectomy (DS) re-operation with subconjunctival and subscleral collagen matrix (Ologen™) and minimal use of mitomycin C in cases of late failure blebs. Methods: A prospective evaluation of consecutive patients on which same-site DS was performed with subconjunctival and subscleral collagen matrix (Ologen™) and minimal use of mitomycin C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…9,13 Similar to our study, Díaz-Aljaro demonstrated a significant IOP and medication use reduction in 25 patients who underwent ssDS. 13 Mean IOP reduction was greater with same-site TRAB compared to ssDS (20.31% vs 37.9% reduction); however, mean preoperative IOP was also greater in the current study (24.90 vs 20.88 mmHg). Concerning mean medication use reduction, same-site TRAB outcomes were superior (80.36% vs. 67.27% reduction) but preoperative medication use was also greater (2.8 vs 2.2 medications).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…9,13 Similar to our study, Díaz-Aljaro demonstrated a significant IOP and medication use reduction in 25 patients who underwent ssDS. 13 Mean IOP reduction was greater with same-site TRAB compared to ssDS (20.31% vs 37.9% reduction); however, mean preoperative IOP was also greater in the current study (24.90 vs 20.88 mmHg). Concerning mean medication use reduction, same-site TRAB outcomes were superior (80.36% vs. 67.27% reduction) but preoperative medication use was also greater (2.8 vs 2.2 medications).…”
Section: Discussionsupporting
confidence: 84%
“…[9][10][11]13 Surgical reopening of the failed blebs could be advantageous because conjunctiva can be preserved for future surgeries, although operating in a previously used surgical field may be challenging due to excessive scarring and bleeding. 9,13 Similar to our study, Díaz-Aljaro demonstrated a significant IOP and medication use reduction in 25 patients who underwent ssDS. 13 Mean IOP reduction was greater with same-site TRAB compared to ssDS (20.31% vs 37.9% reduction); however, mean preoperative IOP was also greater in the current study (24.90 vs 20.88 mmHg).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations